Pelaksanaan Peran Kantor Wilayah Kementerian Hukum Dan Ham Sumatera Barat Dalam Rangka Harmonisasi Peraturan Daerah Provinsi Sumatera Barat Tahun 2019 - Delfina Gusman; Alsyam Alsyam; Didi Nazmi (UIR Press, 2021)
The Regional Offices of the Ministry of Law and Human Rights in each region have an important role in the harmonization of regional regulations in accordance with the legal hierarchy. Harmonization of law is an effort to create a harmony, suitability and compatibility to balance the legal norms. One of the agencies that has this role is the Ministry of Law and Human Rights to each region. The results of the study show that in relation to the duties and functions of the Regional Office, basically the duties and functions of the Regional Office in preparing regional regulations are in line with the provisions of Law Number 12 of 2011 concerning the Establishment of Legislation. the invitation, but the involvement of the Regional Office of the Ministry of Law and Human Rights is limited and passive waiting for the local government and DPRD to participate. In an effort to increase the role of the Regional Office of the Ministry of Law and Human Rights in the process of drafting regional regulations, it is necessary to formulate a rule for implementation that regulates in detail the mechanism for the preparation of regional regulations involving the Regional Government, DPRD and Regional Office of the Ministry of Law and Human Rights. optimizing the preparation of quality regional regulations.